1991
DOI: 10.1083/jcb.114.1.21
|View full text |Cite
|
Sign up to set email alerts
|

ER translocation intermediates are adjacent to a nonglycosylated 34-kD integral membrane protein.

Abstract: Abstract. We have used the homobifunctional crosslinking reagent disuccinimidyl suberate (DSS) to identify proteins that are adjacent to nascent polypeptides undergoing translocations across mammalian rough ER . Translocation intermediates were assembled by supplementing cell free translations of truncated mRNAs with the signal recognition particle (SRP) and microsomal membrane vesicles . Two prominent crosslinked products of 45 and 64 kD were detected . The 64-kD product was obtained when the cell free transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…We have used a photocross-linking approach to identify these components and found that the major photocross-linking partner of nascent type I and type II signalanchor proteins is an integral membrane protein denoted Sec61~ [7]. Other groups have identified non-glycosylated proteins of between 34 and 39 kDa as being adjacent to nascent membrane proteins during insertion into the ER [8,9]. Although formal identification of these proteins remains to be made it seems likely that these proteins are Sec61~.…”
Section: Introductionmentioning
confidence: 99%
“…We have used a photocross-linking approach to identify these components and found that the major photocross-linking partner of nascent type I and type II signalanchor proteins is an integral membrane protein denoted Sec61~ [7]. Other groups have identified non-glycosylated proteins of between 34 and 39 kDa as being adjacent to nascent membrane proteins during insertion into the ER [8,9]. Although formal identification of these proteins remains to be made it seems likely that these proteins are Sec61~.…”
Section: Introductionmentioning
confidence: 99%
“…However, several investigators have provided evidence that the ER membrane glycoproteins TRAM and the Sec61p complex are components of the mammalian ER translocon that participates in protein translocation (2). These translocon proteins may associate with ER proteins during the translocation of secretory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This protein-conducting channel consists of ER-associated proteins forming a translocon, which includes the translocon-associated protein, the translocating chain-associating membrane protein (TRAM) and the Sec61p complex (1,2). TRAM and Sec61p are tightly associated with membrane-bound ribosomes, suggesting that polypeptide nascent chains pass directly from the ribosome into a protein-conducting channel (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sec61α is the largest component of the complex, spanning the membrane 10 times. The use of photo-crosslinking in tandem with modified mRNAs encoding cross-linkable and prematurely truncated polypeptides has shown that Sec61 is intimately associated with the translocating polypeptide (Mothes et al, 1994) (Kellaris et al, 1991) (High et al, 1993). Diffusion studies have suggested that the pore has a size of 40 to 60 Å (Hamman et al, 1997).…”
Section: Protein Targeting To the Ermentioning
confidence: 99%